(untitled) (INNOTEC, 2013)
In the last years it has been worked on the concept of Biomasic as an alternative to Petroquimic. An increasing interest of renewable resources in the area of energy and materials exists. In this work the synthesis of new polymeric materials derived from several renewable sources with emphasis in the valuation of lignins, with an oxidative systems enzymatic presents in two stocks of fungi G. trabeum and P. ostreatus in different combinations starters, were studied. The purpose was the optimization and modeling of the enzimatic production by semi solid fermentation process. The activity on Kraft and Organosolv lignins was analized and it was observed diminution of the molecular weight and an increase of the carbonyl groups in the tests with models and with lignins. We conclude that for both fungus the origin of the lignin as a carbon source is irrelevant. We consider that the production of standardized enzymatic extracts can be an interesting contribution at the time of making modifications in industrial lignins to obtain “well-known functional units”. In future works the kinetic of modification will be studied with the objective to make possible a future industrial application.